Influence of Turgor Pressure Manipulation on Plasmalemma Transport of HCO(3)(−) and OH(−) in Chara corallina - Lucas, William J. (1981)
A modified version of the osmotic shock technique was used to investigate HCO(3)(−) and OH(−) transport in the alga Chara corallina. Cell turgor was brought close to zero and then restored. When turgor was reduced to near the plasmolytic point using an osmoticum, little effect was observed on H(14)CO(3)(−) assimilation and OH(−) transport. However, when turgor was recovered in these cells, there was a large reduction in HCO(3)(−) and OH(−) transport activity. In contrast, when cells were air-dried to zero turgor, and rewetted to restore turgor, no significant effect on OH(−) transport was observed. The effect of plasmolysis was also studied. When Chara cells were plasmolyzed, in most cases, all OH(−) transport activity was lost and acidification was observed along the cell surface. None of the above treatments had any long term effect on cyclosis. These results are discussed with respect to present concepts of turgorinduced changes in membrane functions.